Biochemic System of Medicine - A Boon to Homoeopathy BIO = LIVING (LIFE), CHEMIC = CHEMICAL (Homoeopathy for All, 2025)
A German physician Dr. Schussler  realized that a deficiency of certain  tissue salts can lead to a number  of diseases. These salts are normal  components of healthy tissues  are essential for the growth and  development of the body. Although  this system is considered to be an  offshoot of Homoeopathy, it has  its independent standing. It means  chemical activity in living or life.
Keywords: German; physician; deficiency; certain; tissue; salts